The message of the Fathers of Church for the contemporary preaching - Kazimierz Panuś (Ruch Biblijny i Liturgiczny, 2008)
By reading the sermons and homilies of the Fathers of Church worked out in the golden patristic period one can still learn how to advocate the word of God in a vivid, popular, illustrative, current and profound way. The Fathers of Church are absorbed in the Holy Scriptures, well-thought-out, prayed for and deeply studied. Holding the Holy Scriptures in hand they try to understand the world around and to find a place for themselves as well as for the people entrusted to them. They diligently listen to the Holy Scriptures because it is the Word of God directed also to them. What they give to their listeners is supported by clear testimony of their lives.